GNP, Inequality, and Education: An Empirical Study of Rural Poverty - Lola Oktaviani; I Wayan Suparta (International Journal of Economics and Management Sciences, 2025)
This study aims to analyze the effect of Agricultural GDP, Gini Ratio, and Education in influencing poverty in western Indonesia. A panel data model with Fixed Effect Model estimation was used for data of 17 provinces from 2019 to 2023. The results showed that partially the Agricultural sector GRDP had a significant negative effect, inequality with the Gini Ratio indicator had a significant positive effect, while education with the average years of schooling indicator had a negative but insignificant effect. These findings indicate that an increase in agricultural output and education can reduce poverty, while high income inequality can worsen poverty conditions in rural areas.